Meio ambiente e políticas públicas : o caso das Reservas Particulares do Patrimônio Natural (RPPN) de Monte Alto - SP - Nascibem, Fábio Gabriel, 1993- (2024)
Orientadores: Alessandra Aparecida Viveiro, Oswaldo Gonçalves Junior